EFL PRE-SERVICE TEACHERS’ PERCEPTION IN MANAGING THE LEARNING PROCESS DURING KAMPUS MENGAJAR PROGRAM - Muhammad Asrafil Husein La Ede; Maulina Maulina; Faridawati Faridawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Kampus Mengajar program as one of Merdeka Belajar-Kampus Merdeka (MBKM) programs initiated by the Minister of Education and Culture of the Republic of Indonesia in 2020 is one of the programs that increase the professionalism of students as prospective teachers in Indonesia. Therefore, this study aims to determine the Perception of EFL Pre-service Teachers in Managing the Learning Process during Kampus Mengajar Program. By using a qualitative descriptive design, six pre-service teachers of the English education study program at the Muhammadiyah University of Kendari were interviewed as alumni of Kampus Mengajar program batch I. The results of this study indicate that participants have a positive perception of Kampus Mengajar program to improve their competence as pre-service EFL teachers. However, in the results of the study, there were also many obstacles faced by participants such as difficulties in designing learning caused by differences between basic education taken during lectures and subjects taught during teaching, difficulties in classroom management, and also difficulties in communication caused by differences culture. Despite that, Kampus Mengajar program is highly recommended to be implemented in teacher education by students and should be encouraged by universities.